Fabrication of Low Impedance Ti/Au Multielectrode Arrays Through Substrate Elasticity Control for Flexible Neural Implant - Park, HyungDal; Choi, Won suk; Oh, SungHwan; Seok, Seonho; KIM, JIN SEOK (28th edition of the Symposium on Design, Test, Integration & Packaging of MEMS and MOEMS (DTIP 2025), 2025)
This paper presents an innovative approach to fabricate flexible neural electrodes with the key characteristics of low impedance and high adhesion. This achievement is realized through a two-step process: first, a thin film metallization process is applied to a partially cured photosensitive polyimide (PSPI) substrate, followed by a full curing process after metal electrode patterning. The proposed method harnesses metal intermixing with the flexible polymer substrate to enhance adhesion. while also utilizing hightemperature curing to rectify lattice defects within the metal thin film, leading to a notable reduction in impedance. The increase in metal adhesion is empirically confirmed through a scotch tape adhesion test. Furthermore, the effectiveness of impedance reduction is supported by electrochemical characterization, including impedance and phase measurements after complete polymer substrate curing. The impedance of the newly developed flexible neural electrodes is measured at 9.96 kΩ at a frequency of 1 kHz, a marked improvement compared to conventional PSPI-cured electrodes, which exhibit 36.24 kΩ impedance at the same frequency.